Don't rent my room! - Angell, Judie (New York : Bantam Books, 1990)
Fifteen-year-old Lucy is apprehensive about leaving the city for the country when her parents decide to run an inn on the New England coast.
Booklist.
Bulletin (Center for Children's books).
School Library Journal.
6.8
6.8
7-10.
Keywords: Country life -- Fiction; Family life -- Fiction; Hotels, motels, etc. -- Fiction; Country life -- Fiction; Family life -- Fiction; Hotels, motels, etc. -- Fiction